2024
DOI: 10.3847/1538-4357/ad3643
|View full text |Cite
|
Sign up to set email alerts
|

Active Galactic Nuclei Selection and Demographics: A New Age with JWST/MIRI

Jianwei 建 伟 Lyu 吕,
Stacey Alberts,
George H. Rieke
et al.

Abstract: Understanding the coevolution of supermassive black holes and their host systems requires a comprehensive census of active galactic nuclei (AGNs) behavior across a wide range of redshift, luminosity, obscuration level, and galaxy properties. We report significant progress with JWST toward this goal from the Systematic Mid-infrared Instrument Legacy Extragalactic Survey (SMILES). Based on comprehensive spectral energy distribution (SED) analysis of 3273 MIRI-detected sources, we identify 217 AGN candidates over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 160 publications
0
13
0
Order By: Relevance
“…Our final sample includes 14 sources studied in Williams et al (2023a), as well as two sources included in the sample of highredshift obscured AGN candidates presented in Lyu et al (2024), one source identified as an AGN in Matthee et al (2024), and five galaxies selected as high-redshift candidates in Hainline et al (2024b). Compared to the galaxies in common with Williams et al (2023a), the sample in this paper is 0.5 mag fainter in F444W (medians and quartiles 26.5 26.0 27.5 mag versus 26.0 25.4 26.9 mag), and bluer in F277W-F444W (+ + + 1.3 1.1 1.7 mag versus + + + 1.6 1.5 2.5 mag) and F150W-F200W (+ -+ 0.0 0.1 0.2 mag versus + + + 0.2 0.0 0.3 mag).…”
Section: Nircam-based Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our final sample includes 14 sources studied in Williams et al (2023a), as well as two sources included in the sample of highredshift obscured AGN candidates presented in Lyu et al (2024), one source identified as an AGN in Matthee et al (2024), and five galaxies selected as high-redshift candidates in Hainline et al (2024b). Compared to the galaxies in common with Williams et al (2023a), the sample in this paper is 0.5 mag fainter in F444W (medians and quartiles 26.5 26.0 27.5 mag versus 26.0 25.4 26.9 mag), and bluer in F277W-F444W (+ + + 1.3 1.1 1.7 mag versus + + + 1.6 1.5 2.5 mag) and F150W-F200W (+ -+ 0.0 0.1 0.2 mag versus + + + 0.2 0.0 0.3 mag).…”
Section: Nircam-based Selectionmentioning
confidence: 99%
“…This code uses a set of semiempirical AGN SED models, which have been optimized for AGN identification and characterization (Lyu et al 2022(Lyu et al , 2024. For this work, we adopted a similar model configuration as in Lyu et al (2024) for the SMILES+JADES AGN identification: the AGN component includes both the AGN-powered continuum from the UV to the far-IR and the narrow and broad emission lines from the UV to the NIR derived based on empirical observations. The continuum shape and line strengths of the AGN SED can be modified by a hybrid extinction configuration featuring the SMC-like curve for the commonly seen UVoptical extinction in Type-1 AGNs and an empirical attenuation law for the IR obscuration.…”
Section: The Prospector-agn+ Codementioning
confidence: 99%
See 1 more Smart Citation
“…With the improved sensitivity and wavelength coverage of JWST data, significant progress has been made to identify AGN. Based on a semiempirical SED analysis of MIRIdetected sources with JADES NIRCam and SMILES MIRI photometry, Lyu et al (2024) have drastically improved the AGN census in the central regions of GOODS-S. For our sample, three new AGN candidates have been revealed from that study: JADES IDs 57356, 106502, and 204851. Notably, ID 204851 has been confirmed to be a broad-line AGN at z = 5.48 in FRESCO data (Matthee et al 2023).…”
Section: Possible Evidence Of Active Galactic Nuclei Among Red Galaxiesmentioning
confidence: 99%
“…We find that 13 out of 66 objects in the NIRCam footprint are candidate LRDs by these criteria (nine of which lie in our MIRI coverage, excluding the probable brown dwarf candidate, ID 190413). Two of the 13 include sources with evidence of an AGN, including ID 204851 (Lyu et al 2024;Matthee et al 2023), as well as ID 154428, which show possible evidence of broadened Hα and a weak narrow component in FRESCO data (F. Sun et al 2024, in preparation). While we do not fold in the explicit compactness cut of Greene et al (2023) to identify LRDs, we note that all candidates identified by the LRD colors are visibly unresolved, or consistent with point sources, in F444W (including ID 204851, which in the single-band cutouts of Figure 11 appears blended with two neighbors).…”
Section: Possible Evidence Of Active Galactic Nuclei Among Red Galaxiesmentioning
confidence: 99%